Extender development for optimal cryopreservation of buck sperm to increase reproductive efficiency of goats - Bodu, Mustafa; Hitit, Mustafa; Greenwood, Olivia Chika; Murray, Raheem Davian; Memili, Erdogan (Frontiers in Veterinary Science, 2025)
Preservation of sperm significantly contributes to the advancement of assisted reproductive technologies, genetic conservation and improvement efforts, and precision breeding of livestock. This review distills knowledge from the existing information and emerging patterns in the field of buck sperm cryopreservation. The primary focus is on the challenges and opportunities associated with improving extender formulations and freezing techniques in order to enhance the vitality of sperm after thawing and to increase the potential for conception. This review assesses the efficacy and limitations of conventional extenders derived from egg yolk or soybean lecithin, and the adverse impacts of seminal plasma enzymes on sperm quality during the processes of chilling and cryopreservation. Significant progress has been made in the fields of molecular biology namely lipidomics, proteomics, metabolomics, DNA methylation providing valuable knowledge regarding the unique reactions of sperm to cryopreservation. The utilization of the “omics” technologies has shown intricate molecular transformation that occur in sperm during freezing and thawing. Moreover, detection of molecular biomarkers that indicate the quality of sperm and their ability to withstand freezing provides opportunities to choose the best sperm samples for cryopreservation. This, in turn, enhances the results of artificial insemination and genetic conservation endeavors. This review emphasizes the necessity for adopting a comprehensive approach that combines molecular and cellular knowledge with practical methods in the field of sperm cryopreservation to ensure production of goats as major food animals in the global scale.